New lands, new languages: navigating intersectionality in school leadership - Fuller, Kay (Frontiers Media, 2018)
In the global context of deepening social and political divisions and at a time of growing forced displacement of people due to conflict, there is an ever increasing need for educators and school leaders to understand issues relating to equality and diversity with respect to themselves and the students with whom they work. In particular, the intersecting characteristics that make up individual and collective identities simultaneously afford opportunities and inflict oppressions depending on circumstances and context. This paper focuses on a theorisation of intersectionality as simultaneity through an analysis of linguistic exchanges as they reveal fluctuations of empowerment and disempowerment in the context of culturally and linguistically responsive school leadership. It draws on research findings from the English case as part of an international comparative project focused on Black women principals’ experiences of leading schools in England, South Africa and the United States of America. It reports an account of a British Pakistani Muslim woman’s experience of school leadership as she negotiated a discussion of institutional racism in a school serving a multi-ethnic population of students. Using Bourdieu’s linguistic concepts, I argue that a fine grained analysis of a series of reported linguistic exchanges with multiple stakeholders reveals how various members of the school community accepted or resisted her authority to use official language. There is no guarantee that linguistic habitus will convert into linguistic capital. Moreover, I argue that educators and school leaders need to understand intersectionality as simultaneity so they can navigate identity, institutional and social practices in relation to school leadership and the education of minoritised students.